2019
DOI: 10.1111/bcp.14019
|View full text |Cite
|
Sign up to set email alerts
|

The relative lethal toxicity of pharmaceutical and illicit substances: A 16‐year study of the Greater Newcastle Hunter Area, Australia

Abstract: Aims We aim to calculate 2 metrics of relative lethal toxicity; the fatal toxicity index (FTI; number of deaths per year of a daily dose) and the case fatality (CF; number of deaths per overdose) with a focus on opioids, antidepressants, antipsychotics, benzodiazepines and illicit drugs. Methods This descriptive cohort study used the Australian National Coronial Information System (NCIS) to identify a population of individuals with drug‐associated deaths in the Greater Newcastle Hunter Area between January 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
2
22
0
2
Order By: Relevance
“…This might be linked to the absence of fatal ventricular dysrhythmias in these patients. This coincides with Brett et al 48 who reported less likelihood of case fatalities per overdose for most acute antipsychotics poisoning, particularly the atypical ones.…”
Section: Discussionsupporting
confidence: 90%
“…This might be linked to the absence of fatal ventricular dysrhythmias in these patients. This coincides with Brett et al 48 who reported less likelihood of case fatalities per overdose for most acute antipsychotics poisoning, particularly the atypical ones.…”
Section: Discussionsupporting
confidence: 90%
“…A vigilância ao uso dos agrotóxicos é necessária para o monitoramento das atividades que envolvem esses compostos, desde a produção, o transporte, o armazenamento, a comercialização até o uso. O registro das intoxicações atendidas por centros de informação e assistência toxicológica (CIATox) constitui fonte significativa para o monitoramento na etapa pós-comercialização dos produtos e é empregado rotineiramente em países desenvolvidos 4,5 .…”
Section: Introductionunclassified
“…In the other Nordic countries, Norway [8] and Denmark [9], methadone has also been found to contribute to overdose mortality. Methadone has a higher fatal toxicity index (drug‐specific mortality rate to prescription rate) than other opioids [10,11]. In the United States before the opioid overdose epidemic during the last decade, methadone was implicated in one‐third of the opioid‐related overdose deaths, although the drug represented less than 5% of the opioid prescriptions dispensed at that time [12].…”
Section: Introductionmentioning
confidence: 99%